Improvements of the Design Process in the Microwave Transistors Industry - Rafael-Valdivia, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper presents a technique to improve the design process of microwave transistors based on two aspects: an improved design of experiment test (DOE), and an electro-thermal enhanced model (MET). The DOE test allowed us to center the design through variations in specific parameters, avoiding complex electromagnetic simulations of mutual coupling between the wires inside the transistor, which generally, in conventional CAD tools present a high computational cost. The electro-thermal model, enhanced by using the effective voltage approach, allowed us to predict not only the self-heating phenomena, but also the appropriate impedances for transistor´s maximum output power and maximum efficiency. In this way it was possible to select the operating conditions which can warrant low self-heating and the best trade-off between power, efficiency and linearity. The presented techniques are specifically important for the implementation of power amplifiers for the future wireless communication systems which must be designed to operate with broad band signals. The combination of our proposed techniques can allow the reduction of the design time and associated costs at industrial level. The improved design of experiment permitted to center the design of the transistor, making sure that the designer can get the best performances of the transistor. The thermal characterization allows to make sure that the microwave transistor operates below the maximum allowed temperature in a built power amplifier, which warrants the reliability of the system.